Him a poet and boy he know it - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
We thought we'd seen them all. Often a seminar produces stylish speeches and lyrical recommendations, but we'd never seen a participant's poem as the summary report of a meeting (although Spore Mailbox does receive readers poems regularly).Maybe it...